Quo Vadis International Trade: Indonesian Diplomacy Strategy Regarding Settlement WTO with South Korea - Muhammad Ridha Iswardhana (Jurnal Ilmiah Hubungan Internasional, 2018)
The trade relation among countries does not necessarily benefit all members, in that case it so common for issue to arise that often turns to be dispute. Interestingly, the role of WTO somehow does not fulfill the gap, sometimes it is necessary to add additional mechanism to resolve the dispute. At the end the result can be obtained by the members.This research focuses on the diplomacy process between Indonesian and South Korea regarding the dumping issue on paper commodity. It should be noted that South Korea has not fully implemented the obligation after DSB Appellate Body’s decision on 2005 and 2007. As for the research question, this research comes out with “what is the strategy imposed by Indonesian government to settle the dispute on paper dumping?”. Trade diplomacy and linkage theory will be used as foundation to deepen the analysis.